CHI '14 Extended Abstracts on Human Factors in Computing Systems 2014
DOI: 10.1145/2559206.2578865
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on a synergistic format for disseminating research through design

Abstract: CHI is more than a conference, it is an international community of researchers and practitioners who want to make a difference. Everything we do is focused on uncovering, critiquing and celebrating radically new ways for people and technology to evolve together. People in their everyday contexts, in diverse regions of the world, from very different backgrounds, with alternative outlooks on life drive this innovation. As you take part in the conference sessions we really hope you will experience how powerful th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The study reported on in this paper is a part of a longitudinal Research-through-Design (RtD) [20,47,55] programme of work (ongoing for three years at the time of this study) exploring how IoT can be configured in creative ways to offer children in a wider age range (i.e. zero to nine years old) new opportunities to free play together outdoors.…”
Section: Our Inquirymentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported on in this paper is a part of a longitudinal Research-through-Design (RtD) [20,47,55] programme of work (ongoing for three years at the time of this study) exploring how IoT can be configured in creative ways to offer children in a wider age range (i.e. zero to nine years old) new opportunities to free play together outdoors.…”
Section: Our Inquirymentioning
confidence: 99%
“…In our work on a funded, UK-based, Research-through-Design (RtD) [20,27,47,55] project, we have been exploring the Interaction Design opportunities for supporting children's outdoor free play via programmable IoT devices that are now widely available for children. Engaging with extant work, we recognise the importance of studying prototypes in real world outdoor environments, by considering, for example, how outdoor play incorporates its topographical features (such as trees, walls, and open spaces).…”
Section: Introductionmentioning
confidence: 99%
“…We wish now to turn to matters of design. The work that we are producing within our research sits squarely within an emerging community of practitioner-researchers who engage in Research Through Design [14,50]. This is becoming of increasing interest to the HCI community [16,39], and resonates with our work because of the potential value of making design interventions and material explorations explicitly as a form of inquiry [16], with materiality being so important to an understanding of domestic spaces [30].…”
Section: Design Positioningmentioning
confidence: 99%
“…However, there remains concern that the objects themselves are underappreciated: in recent years, there has been increased effort to consider the role of 'things' in HCI research, recognising that "the things of design research have remained conspicuously overlooked, under-engaged with, and, for the most part, absent from the CHI conference" [28]. The CHI workshop series on this topic [28], the Pictorials track at DIS and the Research through Design conference [41] represent different avenues for thinking more about the role of prototypes and other 'things' in our research.…”
Section: Introductionmentioning
confidence: 99%